Temporally resolved parametric assessment of Z-magnetization recovery (TOPAZ): dynamic myocardial T1 mapping using a cine steady-state look-locker approach - Weingärtner, Sebastian; Rieger, Benedikt; Schad, Lothar R. (Magnetic resonance in medicine, 2018)
Purpose To develop and evaluate a cardiac phase-resolved myocardial T1 mapping sequence. Methods The proposed method for temporally resolved parametric assessment of Z-magnetization recovery (TOPAZ) is based on contiguous fast low-angle shot imaging readout after magnetization inversion from the pulsed steady state. Thereby, segmented k-space data are acquired over multiple heartbeats, before reaching steady state. This results in sampling of the inversion-recovery curve for each heart phase at multiple points separated by an R-R interval. Joint T1 and estimation is performed for reconstruction of cardiac phase-resolved T1 and maps. Sequence parameters are optimized using numerical simulations. Phantom and in vivo imaging are performed to compare the proposed sequence to a spin-echo reference and saturation pulse prepared heart rate-independent inversion-recovery (SAPPHIRE) T1 mapping sequence in terms of accuracy and precision. Results In phantom, TOPAZ T1 values with integrated correction are in good agreement with spin-echo T1 values (normalized root mean square error = 4.2%) and consistent across the cardiac cycle (coefficient of variation = 1.4 ± 0.78%) and different heart rates (coefficient of variation = 1.2 ± 1.9%). In vivo imaging shows no significant difference in TOPAZ T1 times between the cardiac phases (analysis of variance: P = 0.14, coefficient of variation = 3.2 ± 0.8%), but underestimation compared with SAPPHIRE (T1 time ± precision: 1431 ± 56 ms versus 1569 ± 65 ms). In vivo precision is comparable to SAPPHIRE T1 mapping until middiastole (P > 0.07), but deteriorates in the later phases. Conclusions The proposed sequence allows cardiac phase-resolved T1 mapping with integrated assessment at a temporal resolution of 40 ms. Magn Reson Med 79:2087-2100, 2018. © 2017 International Society for Magnetic Resonance in Medicine.